Food prices and inflation dynamics in China. Issue 3 (26th August 2014) - Zhang, Chengsi; Meng, Chunming; Getz, Lisa
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – China has witnessed low and stable consumer price inflation in conjunction with high and volatile food price inflation over the past decade. The purpose of this paper is to examine questions about whether or not the link between consumer price inflation and food price inflation has weakened and the determinants of consumer price inflation. Design/methodology/approach – This paper explores these questions by estimating error correction terms for monetary and external sectors using the Johansen cointegration method. Findings – Empirical results suggest that the link between consumer price inflation and food prices has not been weakened, food price inflation, especially cereal price inflation, remains a significant driving force for overall consumer price inflation, and international food prices also play a significant role in determining China's inflation dynamics. Originality/value – The paper construct a multivariate dynamic model that features the link between consumer price inflation and its potential driving variables. It also develops error correction models for food price, non-food price and consumer price inflation, which can accommodate dynamic interactions among the underlying variables.